Digestive characteristics of oil body extracted from soybean aqueous extract at different pHs. (November 2022) - Yang, Xufeng; Wu, Yingying; Liu, Yang; Ding, Xiuzhen; Zhang, Dajian; Zhao, Luping
Graphical abstract: Highlights: Extrinsic proteins, particle sizes and charges decreased with extraction pH 5.0–11.0. Oleosins were completely hydrolyzed in stomach phase (SGF). The pH 9.0-, 11.0-SOB emulsions without extrinsic proteins coalesced easily in SGF. Total FFA release of pH 7.0-SOB emulsion was highest (70.5%) in intestinal phase. Abstract: Soybean oil bodies (SOBs), a natural source of pre-emulsified oil, have important potential applications in food industry. In this study, SOBs were extracted from raw soybean milk at pH 5.0, 7.0, 8.0, 9.0 and 11.0. The pH 5.0-, 7.0- and 8.0-SOB contained extrinsic proteins (mainly 7S, 11S and γ-conglycinin) and oleosins (24 kDa, 18 kDa and 16 kDa), and pH 9.0-, 11.0-SOB only had oleosins. Extrinsic protein contents decreased from 83.9% at pH 5.0-SOB to 58.2% at pH 8.0-SOB, zeta potentials increased gradually from –21.7 mV to –14.67 mV and particle sizes decreased from 924 nm to 359 nm with increasing extraction pHs. In stomach digestion, oleosins of pH 5.0-, 7.0-, 8.0-SOB were hydrolyzed more rapidly than extrinsic proteins. All 24 kDa oleosins were hydrolyzed during 5 min, and 18 kDa oleosins were completely hydrolyzed at 30 min for all SOBs. Oleosins were hydrolyzed and produced <15 kDa pepsin-resistant peptides. In addition, some 7S and 11S of pH 5.0-, 7.0-, 8.0-SOB resisted pepsin hydrolysis. For all SOB emulsions, zeta potentials decreased and the droplets sizes increased significantly (P < 0.05) with the extension of gastric digestive time. The oil droplets of all SOB emulsions aggregated, and the coalescence of oil droplets more easily occurred in pH 9.0- and 11.0-SOB emulsions. During the intestinal phase, zeta potentials and diameters of the droplets decreased gradually, and the droplets of SOB emulsions dispersed according to the CLSM. FFA release rates of pH 5.0-, 7.0-, 8.0-SOB emulsions increased rapidly and then increased slowly, however, the release tendency of pH 9.0-, 11.0-SOB emulsions were opposite. Total FFA releases of pH 5.0-, 7.0-, 8.0-, 9.0-, 11.0-SOB emulsions were respectively 52.5%, 70.5%, 59%, 48.8%, 43.3% at 180 min. Therefore, the digestive behaviors of SOB emulsions extracted at different pHs were different. This study will provide guidance for SOB products.